2014
DOI: 10.3109/0886022x.2013.875834
|View full text |Cite
|
Sign up to set email alerts
|

Kidney growth and renal functions under the growth hormone replacement therapy in children

Abstract: Objective: The aim of this study was to investigate the kidney growth and renal functions in children receiving recombinant human growth hormone (rhGH) treatment. Materials and methods: A total of 37 children who received rhGH for 1.5 years before the study was started and 48 healthy controls were included at first evaluation. Hormone levels were determined and kidney sizes were measured by ultrasound. Kidney functions were assessed by serum creatinine and estimated glomerular filtration rate (eGFR). After 3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
7
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
6
7
2
Order By: Relevance
“…Similar to the current study, a previous study [24] reported non-significant differences in weight values between GH deficient patients and the control. In contrast, the present result disagrees with that of a previous investigation [25]. The reason for the discrepancies between the studies may be related to the sample size,nutritional habits and life style factors.…”
Section: Anthropometric Measurements Of Ghdeficient Patients and The contrasting
confidence: 99%
See 2 more Smart Citations
“…Similar to the current study, a previous study [24] reported non-significant differences in weight values between GH deficient patients and the control. In contrast, the present result disagrees with that of a previous investigation [25]. The reason for the discrepancies between the studies may be related to the sample size,nutritional habits and life style factors.…”
Section: Anthropometric Measurements Of Ghdeficient Patients and The contrasting
confidence: 99%
“…Concerning the present results of BMI,they are similar to those of other studies [24,25] which reported non-significant differences in BMI between the GH deficient patients and the control group,while theyare indisagreement with other reports [29] . The reason might be that BMI depends on the weight and height and thatit is not clear whether there is a similar association between BMI and peak GH level in healthy children [24].…”
Section: Anthropometric Measurements Of Ghdeficient Patients and The supporting
confidence: 92%
See 1 more Smart Citation
“…Although both growth hormone (produced by the anterior pituitary gland) and insulin-like growth factor 1 are growth stimulants for many organs, including kidney, 10,21,67 a key question is why these hormones might be retained after transplantation in the kidney but not the heart, which, in the abdominal heterotopic position, apparently does not continue to grow rapidly. 37,[48][49][50] The fact that the kidney grafts are life-supporting, whereas heterotopic (that is, abdominally placed) heart grafts do not support a vascular circulatory system (and therefore are not fully functional), may be relevant.…”
mentioning
confidence: 99%
“…[4][5][6] Also, in GH deficient children, GH treatment has been shown to increase kidney length and total kidney volume. [7][8][9][10] It is essential to ascertain longitudinal data after cessation of GH treatment, to investigate the possible effects of higher serum IGF-I levels during childhood on GFR in adulthood.…”
Section: Introductionmentioning
confidence: 99%